Endoscopic ultrasound-guided fiducial marker placement for image-guided radiation therapy without fluoroscopy: safety and technical feasibility - Dhadham, Gautamy Chitiki; Hoffe, Sarah; Harris, Cynthia L.; Klapman, Jason B. (Endoscopy International Open, 2016)
Background and study aims: Endoscopic ultrasound (EUS)-guided fiducial marker placement for image-guided radiation treatment (IGRT) is becoming more widespread. Most case series report the procedure performed using fluoroscopy for spatial geometry although the benefits of this are unclear. The aim of our study is to report the technical feasibility, safety, and migration rate of fiducial marker placement in a large cohort of patients with gastrointestinal malignancies who underwent EUS-guided fiducial marker placement for IGRT without fluoroscopy.Patients and methods: A retrospective chart review was performed on all patients referred for EUS-guided fiducial marker placement from 08/1/07 to 7/31/14 at Moffitt Cancer Center. Results: During the study period, 514 patients underwent placement of 1093 gold fiducial markers under EUS-guidance. Two hundred and forty patients with esophageal/gastro-esophageal junction cancer had 405 fiducials placed. In 188 patients with pancreatic ancer, 510 fiducials were placed. In 54 patients with rectal cancer, 103 fiducials were placed and 32 patients had 75 fiducials placed into other gastrointestinal tract lesions. Minor bleeding, which resolved spontaneously, occurred in two patients. Technical difficulty in placing fiducials was noted in 18 patients. Intraprocedural fiducial migration was noted in two patients and only 2/1093 fiducials (.002%) in two esophageal patients migrated as noted on simulation computed tomography scan. Conclusions: EUS-guided fiducial marker placement without fluoroscopy is technically feasible and safe. There were minimal intraprocedure/post-procedure complications. Imaging at the time of simulation also revealed the migration rate to be extremely low. These results may allow for more widespread adoption of EUS-guided fiducial marker placement.